2020
DOI: 10.1021/acsptsci.0c00125
|View full text |Cite
|
Sign up to set email alerts
|

Selective Elimination of Osteosarcoma Cell Lines with Short Telomeres by Ataxia Telangiectasia and Rad3-Related Inhibitors

Abstract: To avoid replicative senescence or telomere-induced apoptosis, cancers employ telomere maintenance mechanisms (TMMs) involving either the upregulation of telomerase or the acquisition of recombination-based alternative telomere lengthening (ALT). The choice of TMM may differentially influence cancer evolution and be exploitable in targeted therapies. Here, we examine TMMs in a panel of 17 osteosarcoma-derived cell lines, defining three separate groups according to TMM and the length of telomeres maintained. Ei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 74 publications
5
11
0
Order By: Relevance
“…The first strategy is the use of ATR inhibitors against ALT+ cell lines, which initially showed great promise as a potential targeted therapy for ALT cancers [ 61 ]. However, a few recent studies challenged the specificity of ATR inhibitors towards ALT cancers [ 183 , 188 , 189 ]. ATR is an important kinase that functions in a variety of DNA damage response (DDR) pathways, including the activation of replication stress checkpoint and HR [ 190 , 191 ].…”
Section: The Development Of Novel Therapiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The first strategy is the use of ATR inhibitors against ALT+ cell lines, which initially showed great promise as a potential targeted therapy for ALT cancers [ 61 ]. However, a few recent studies challenged the specificity of ATR inhibitors towards ALT cancers [ 183 , 188 , 189 ]. ATR is an important kinase that functions in a variety of DNA damage response (DDR) pathways, including the activation of replication stress checkpoint and HR [ 190 , 191 ].…”
Section: The Development Of Novel Therapiesmentioning
confidence: 99%
“…Using the identical inhibitor (VE-821) as well as the same OS cell lines and assays, they argued that Flynn and colleagues’ original findings were confounded by a lack of control for the well-established variable growth rates of the assessed cell lines. Most recently, Goncalves and colleagues demonstrated that ATR inhibitor sensitivity in OS appears to be another TMM-independent therapeutic modality [ 189 ]. Using a panel of eight ALT+ OS and nine ALT− OS, they assessed the efficacy of three ATR inhibitors, AZD-6738, VE-822, and BAY-1895344.…”
Section: The Development Of Novel Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Matched treatment recommendations based on genomic profiling and in vivo PDX drug testing results will be made available, potentially providing patients with individualized cancer treatment options. In the phase 2 clinical study (NCT04417062) proposed by the Dana-Farber Cancer Institute to evaluate the effectiveness of using two drugs (olaparib and ceralasertib) to treat patients with OS that have not responded to conventional treatments, the derivation of PDX models and paired pre/post-treatment tumor samples are included and may offer additional treatment opportunities [ 101 , 102 ].…”
Section: Mouse Pdx Clinical Trials and Co-clinical Trialsmentioning
confidence: 99%